Learning from the implementation of person-centred care: a meta-synthesis of research related to the Gothenburg framework - Forsgren, Emma; Feldthusen, Caroline; Wallström, Sara; Björkman, Ida; Bergholtz, Jana; Friberg, Febe; Öhlén, Joakim (Frontiers in Health Services, 2025)
IntroductionWhile research has shown promising effects of person-centred care (PCC) in a variety of settings, it remains to be systematically implemented in practice. Publications exist on conceptual frameworks for PCC implementation, as well as identified barriers and enablers, but a comprehensive overview of lessons learned from PCC implementation efforts is lacking. The aim of this study therefore is to synthesize research-based empirical knowledge on implementation of PCC using the theoretical foundation of the Gothenburg framework.MethodInterpretive meta-synthesis, using the theoretical framing of the Gothenburg framework for PCC, and implementation science in the context of healthcare services in Sweden.ResultsThe results illuminate that PCC implementation includes three interrelated categories of strategies, more precisely: strategies connected towards creating and safeguarding a person-centred work and care culture, strategies in connection to leaders and change agents, and strategies focused on learning activities and adaption to setting. An ideal of co-creation in partnership is prominent, and both top-down approaches (such as policy) as well as bottom-up approaches (activities/methodologies/tactics) created within services are at play. Implementation strategies are both deliberate and emergent during the implementation process.DiscussionThe synthesis connects to available implementation research in that it highlights the importance of care culture, connected leadership at different levels, and learning activities. While patients and family carers are included as partners in intervention research, their role as leaders and actors for change in implementation efforts is not explicitly described.ConclusionThe combination of deliberate and emergent strategies, movements from top-down and bottom-up in combination with the ideal of co-creation at all levels demonstrates the complexities and iterative nature of PCC implementation. By illustrating this complexity and providing examples of handling practical issues, this study contributes to deeper insights on PCC implementation.